A proposal to develop the role of special education teachers in achieving psychological security for the disabled students - Adel Hussein Ali Mohamed (International Journal of Psychosocial Rehabilitation, 2020)
One of the most important roles that a teacher with special needs must play to achieve the goals of special education for students with special needs is to meet the emotional needs of students, such as the need for security, love, acceptance, social appreciation, and independence. , Role models, etc., and these needs push the individual forward with the intention of achieving the same achievement and his life becomes rich, emotional, emotional and social. The teacher is one of the main components that help the school succeed in raising the conscience of the learner. He is the leader of the educational and educational work within him, and he is like the investor who invests and directs the gifts in the school environment of human and material gifts that the learner can reach to the highest quality, especially if this teacher deals with students with special needs, and with the category that you need to deal With a special type, and the current study relied on the descriptive analytical approach to reach a A proposal to activate the emotional special education teacher role with students with special needs.